Prospective study on sonographic measurement of umbilical cord thickness, foetal fat layer, interventricular septal thickness as predictors of macrosomia in fetus of women with gestational diabetes mellitus - N., Janani; D., Vimala; N., Gayathri (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The objectives of the study were to evaluate the Prediction of foetal macrosomia based on sonographic measurements of foetal fat layer, Interventricular septal thickness and umbilical cord thickness in Gestational Diabetes Mellitus at term. Methods: After assessment of inclusion and exclusion criteria 100 antenatal women of gestational age more than 37 weeks selected for study in the Department of Obstetrics and Gynaecology of Vinayaka Mission’s Kirupananda variyar medical college and hospital, Salem. Participants underwent a third trimester scan and three extra measurements i.e. Umbilical cord thickness, Interventricular septal thickness and foetal fat layer are measured in addition to the normal examination. Results: In present study umbilical cord thickness had good sensitivity and negative predictive value. Hence, if umbilical cord thickness is less than 90th centile the chance of macrosomia is less, the cut off of foetal fat layer ≥5 mm as predictor of macrosomia had sensitivity of 84.2% and specificity of 86.4% and cut off of Interventricular septal thickness ≥3.9mm as a predictor of macrosomia had sensitivity of 84.2%, specificity of 64.2%, negative predictive value of 95.9%. Thus, interventricular septal thickness and foetal fat layer is a reliable predictor of macrosomia. Conclusions: From this study authors concluded that Umbilical cord thickness, foetal fat layer and Interventricular septal thickness are good predictors of foetal macrosomia. In the assessment of risk of macrosomia in addition to the ultrasonographic measurements the clinical risk factors must be considered.